Complaint reduction in Australian federal policing in the Australian Capital Territory. (3rd September 2018) - Prenzler, Tim; Briody, Michael
Abstract: Across fifteen years to 2015–2016 the rate of public complaints against police in the Australian Capital Territory fell by an extraordinary 79%. This was a much larger and longer-term reduction in complaints than occurred anywhere else in Australia, and it is very unusual in the international policing literature. The paper attempts to examine the nature of this change in greater detail, and possible factors that may have influenced the change. Unlike some other studies, however, there was limited evidence of specific point-in-time innovations that may have affected the trend. Nonetheless, it is likely that a range of reforms in policing influenced the change, with possible lessons for other departments struggling with significant complaint problems. The main reforms included improved custody procedures, greater attention to ethics in recruitment and training, a complaints system focused on managing officer behaviour, enlarged external oversight, and more attention to de-escalation skills in use-of-force training.